Fremanezumab and its isotype slow propagation rate and shorten cortical recovery period but do not prevent occurrence of cortical spreading depression in rats with compromised blood–brain barrier. Issue 5 (May 2020) - Melo-Carrillo, Agustin; Schain, Aaron J.; Stratton, Jennifer; Strassman, Andrew M.; Burstein, Rami
Abstract : Abstract: Most centrally acting migraine preventive drugs suppress frequency and velocity of cortical spreading depression (CSD). The purpose of the current study was to determine how the new class of peripherally acting migraine preventive drug (ie, the anti-CGRP-mAbs) affect CSD—an established animal model of migraine aura, which affects about 1/3 of people with migraine—when allowed to cross the blood–brain barrier (BBB). Using standard electrocorticogram recording techniques and rats in which the BBB was intentionally compromised, we found that when the BBB was opened, the anti-CGRP-mAb fremanezumab did not prevent the induction, occurrence, or propagation of a single wave of CSD induced by a pinprick, but that both fremanezumab and its isotype were capable of slowing down the propagation velocity of CSD and shortening the period of profound depression of spontaneous cortical activity that followed the spreading depolarization. Fremanezumab's inability to completely block the occurrence of CSD in animals in which the BBB was compromised suggests that calcitonin gene-related peptide (CGRP) may not be involved in the initiation of CSD, at least not to the extent that it can prevent its occurrence. Similarly, we cannot conclude that CGRP is involved in the propagation velocity or the neuronal silencing period (also called cortical recovery period) that follows the CSD because similar effects were observed when the isotype was used. These finding call for caution with interpretations of studies that claim to show direct central nervous system effects of CGRP-mAbs. Abstract : Anti-CGRP-mAbs ability to directly alter headache-related peripheral functions in meningeal nociceptors, cerebral, and meningeal blood vessels and possible immune cells, which indirectly alter excitability and responsiveness of neurons in brain areas involved in migraine pathophysiology, is the most likely mechanisms by which this class of drugs prevents migraine.